To assess the aggressiveness of oral squamous cell carcinoma in the young population - Shafqat Ali Shaikh; Syed Akbar Abbas; Muhammad Ehteram Ul Haq; Bushra Ayub; Talha Ahmed Qureshi; Amna Khalil (Journal of the Pakistan Medical Association, 2022)
Introduction: Squamous cell carcinoma of the oral cavity has a high prevalence not only worldwide but also in Asian countries. It has been estimated that the mortality from the tumor has remained almost 56% and cancer presenting at a younger age tends to be more aggressive and advance at the time of presentation. Objectives: To assess the pattern of recurrence and disease-free survival in two age groups. Materials and methods: This is a retrospective, cohort study of patients diagnosed with oral squamous cell carcinoma admitted between 2008 to 2018. Two groups were made with 40 years as a cut off mean. Various etiological factors, staging, treatment, site of the tumor, and recurrence and mortality were assessed. Results: Patients who underwent treatment for the cancer of which 124 patients were of less than 40 years and 327 were of age above 40 years. The ratio between males to females in Age<40 was 5:1 and Age>40 was 3:1 respectively. The most common site of the tumor is cheek in origin. Patients in Age<40 had recurrence of tumor were (n=45, 36%). In Age> 40 years recurrence of tumor is (n=120, 37%) with CI of 95% (P=0.653) and the overall mortality in Age<40 (n=67, 54%) compared to the Age >40 (n=168, 51%) of patients have a mortality with CI of 95% (P=0.811). Conclusion: Overall the study suggests that mortality of the tumor is almost the same with a slight difference in recurrence of the disease. Cheek is the most common site of presentation.